Outcomes post kidney transplantation amongst First Nations Australians in the Northern Territory - Khan, Farhan Ali; Barraclough, Katherine A.; Majoni, Sandawana William; Thomas, Sajan; Munasinghe, Wathsala; Abeyaratne, Asanga; Carroll, Robert (Frontiers in Nephrology, 2025)
Aims1)To compare graft and patient survival rates following deceased donor kidney transplantation in Northern Territory (NT) First Nations Australians between 2001–2011 and 2012-2021. 2)To compare transplant outcomes between First Nations and non-Indigenous Australians during 2012-2021. 3)To assess the impact of eplet mismatches and predicted indirectly recognizable HLA epitopes II (PIRCHE) scores on transplant outcomes in First Nations Australians.BackgroundDespite advancements in transplant outcomes across Australia, uncertainty exists regarding improvements in graft and patient survival rates for NT First Nations Australians. No study has evaluated the impact of molecular matching on post-transplant outcomes for NT First Nations Australians.MethodsWe performed a retrospective cohort study involving NT First Nations Australians transplanted between 2001-2021. Participants were divided into two groups: 2001–2011 and 2012-2021. For comparison, we also included non-Indigenous recipients transplanted during the 2012–2021 period. We analyzed graft and patient survival using Kaplan-Meier curves and assessed the association of eplets and PIRCHE scores with graft outcomes and de novo donor specific antibody (dnDSA) formation.ResultsFive-year graft and patient survival rates were 46% and 66% in the 2001–2011 cohort compared with 69.7% and 83.1% in the 2012–2021 cohort. For non-Indigenous recipients (2012-2021), 5-year graft and patient survival were 90.5% and 97.6%. Higher eplet mismatch loads and PIRCHE scores were not associated with graft survival, patient survival, or time to rejection among First Nations Australians.ConclusionPost-transplant outcomes for First Nations Australians have improved considerably, but they remain inferior to non-Indigenous Australians.